The promotion of civil society in developing countries - the example of European development cooperation - Michael Windfuhr (Deutsches Institut für Entwicklungspolitik (DIE), 1999)
The promotion of civil society has become an important aspect of development cooperation. Most donors have set aside a part of their funds for this task, which is mainly carried out by nongovernmental organizations (NGOs) from donor countries. The European Commission has for a long time been pioneering the promotion of civil society in developing countries. The more democracy, human rights and good governance become central criteria of development cooperation, the more it is faced with the challenge of identifying more precisely the tasks, chances and risks of promoting civil society groups and of coming to an agreement on a meaningful division of labour. The diversity of the functions of civil society and its significance for creating a framework conducive to development are still underrated. The promotion of civil society groups is indispensable if the goals of development cooperation are to be put into practice. Civil society organizations often emerge in the context of conflicts in society. These organizations help to break up decrepit structures, articulate the concerns of disadvantaged groups, and thus promote political participation. In so doing, they contribute to solving social conflicts and to monitoring government action. Despite all enthusiasm for the promotion of civil society in developing countries, potential risks must not be overlooked. In countries where the civil society is still weak, any outside interference has an impact on the development and the composition of civil society. The weaker the society is, the greater the risk that new conflicts emerge when select sections of the population are supported and social interests favoured. External promotion of civil society also requires sensibility because not all civil society activities are automatically conducive to development. Established interest groups, too, organize in a civil society format and block social change. Also, governments in developing countries often try to influence and control development processes in civil society for their own purposes. Development cooperation should not be misled by fake civil society organizations. The development of a diversified civil society is supported by a diversity of partner organizations from industrialized countries. Parallel promotion by NGOs, churches and trade unions, by human rights and environmental groups contribute to the emergence of a pluralist civil society. These players, too, must be aware that their activities might distort the development of civil society or create dependencies.
Keywords: 330